A generalized fractional time series model - Luis A. Gil-Ala\~na (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
We propose in this article a general time series model, whose components are modelled in terms of fractionally integrated processes. This specification allows us to consider the trend, the seasonal and the cyclical components as stochastic processes, including the unit root models as particular cases. A very general version of the tests of Robinson (1994) is used to test the order of integration of each component. Finite-sample critical values of the tests are evaluated and, an empirical application, is also carried out at the end of the article.
urn:nbn:de:kobv:11-10048335
Keywords: C22; 330; Long memory; Time series model; Fractional integration